Irradiation-induced phase change electrolyte and method of making same

CN122907712APending Publication Date: 2026-10-13RES INST OF CHEM DEFENSE PLA ACAD OF MILITARY SCI
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202610824815.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-06-09
Publication Date
2026-10-13

AI Technical Summary

Technical Problem

同时,聚合物固态电解质电化学窗口较窄,对正负极稳定性较差,且均一性不佳

Benefits of technology

1)电解质在液态电解液时适配锂电池:辐照前电解质为液态,具有与液态电解液相同的浸润性和界面接触性,可充分润湿电极表面,降低界面阻抗,适配现有锂电池制造工艺。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122907712A_ABST
    Figure CN122907712A_ABST
Patent Text Reader

Abstract

The application belongs to the technical field of batteries, and specifically discloses an irradiation-induced phase change electrolyte and a preparation method thereof. The electrolyte is irradiated by gamma rays or an electron beam to induce phase change of a liquid electrolyte, and a solid-state electrolyte is formed. The preparation method comprises the following steps: preparing an ester electrolyte system containing a lithium salt; adding an irradiation phase change material and uniformly mixing; irradiating by gamma rays or an electron beam, with an absorbed dose rate of 10-120 Gy / min and an absorbed dose of 0.1-10 kGy. The obtained phase change electrolyte is a liquid electrolyte suitable for lithium batteries before irradiation, and is converted into a solid state after irradiation, and the electrochemical performance remains stable, and the intrinsic safety performance of the battery is significantly improved. The application solves the problems of poor interface contact, difficult processing and low ionic conductivity of traditional solid-state electrolytes, and provides a new technical approach for the intrinsic safety of high-energy-density lithium batteries.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of battery technology, specifically relating to an irradiation-induced phase change electrolyte and its preparation method. Technical Background It is well known that high-energy-density lithium batteries have poorer stability and their safety is more difficult to guarantee. Solid-state batteries are considered the best way to achieve high safety in lithium batteries, especially high-energy-density lithium batteries. Traditional solid-state battery electrolytes are mainly oxides, sulfides, halides, polymers, etc., but they face many unresolved challenges. Oxide solid-state electrolytes have high room-temperature ionic conductivity, reaching 10. -2 With a conductivity of ~1 mS / cm, a wide electrochemical window, good air and thermal stability, and high mechanical strength, oxide electrolytes are ideal solid-state electrolyte materials. However, due to their brittleness, poor processing performance, and poor contact with the electrode interface, oxide electrolytes are currently mainly used in semi-solid-state batteries with added electrolyte. Sulfide electrolytes are derived from oxide solid electrolytes and are classified into crystalline, glassy, ​​and glass-ceramic electrolytes according to their crystal morphology. A typical example of a crystalline solid electrolyte is Thio-LISICON, which has a room temperature ionic conductivity of up to 35 mS / cm, which is 3 to 5 times that of liquid electrolytes. Glass-ceramic electrolytes have a room temperature ionic conductivity between 1 and 12 mS / cm, a wide range of compositional variations, and also have the characteristics of high thermal stability, good safety performance, and electrochemical stability. They have outstanding advantages in high-power and high- and low-temperature solid-state batteries and are one of the most promising solid-state electrolytes. However, sulfide solid electrolytes also have many problems such as easy oxidation, poor chemical stability, and high preparation difficulty. The general chemical formula of halide electrolytes is Lia-M-Clb (M=Metal). Compared to oxides and sulfides, halide electrolytes have theoretical ionic conductivity on the order of 10 mS / cm, exhibit higher redox potentials, and better compatibility with high-voltage cathode materials. However, many scientific issues regarding the material system remain unclear, and core problems such as hygroscopicity and deliquescence exist in applications. Therefore, halide electrolytes are currently mainly focused on basic scientific research, and industrialization is progressing slowly. Traditional polymer solid electrolytes are systems composed of high-molecular-weight polymers, lithium salts, and inorganic plasticizers. Common polymer matrices include ether-based polymers, nitrile-based polymers, siloxane-based polymers, carbonate-based polymers, and vinylidene fluoride polymers. The ionic conductivity of polymer solid electrolytes is generally lower than that of liquid electrolytes, requiring further improvement. Simultaneously, polymer solid electrolytes have a narrow electrochemical window, poor stability to both positive and negative electrodes, and poor uniformity.

[0002] At present, there is an urgent need to explore new ways to realize solid electrolytes and create a new solid-state lithium battery system technology that is intrinsically safe. Summary of the Invention

[0003] The purpose of this invention is to develop a method using gamma rays or electron beams to synthesize an irradiated phase change solid electrolyte for improving the cycle life and safety performance of lithium batteries.

[0004] The technical solution adopted in this invention is as follows: In a first aspect, the present invention provides a method for preparing an irradiated phase change electrolyte, characterized by comprising the following steps: S1: Lithium salt is dissolved in ester organic compounds under an inert atmosphere to obtain an electrolyte containing lithium salt; the lithium salt concentration is 0.5–2 mol / L; The lithium salt is one or a mixture of two or more of lithium hexafluorophosphate (LiPF6), lithium dioxaborate (LiBOB), lithium tetrafluoroborate (LiBF4), lithium bis(difluorosulfonyl)imide (LiFSI), and lithium bis(trifluoromethylsulfonyl)imide (LiTFSI). The ester organic compounds are one or a mixture of two or more of the following: carbonates, carboxylic acid esters, and vinylene carbonates.

[0005] S2: Add the irradiated phase change material to the electrolyte and mix thoroughly to obtain a precursor solution; the mass concentration of the irradiated phase change material in the precursor solution is 20~60 g / L; This concentration range ensures the formation of a gel polymer network with appropriate crosslinking density and mechanical strength after irradiation, while maintaining high ionic conductivity; The irradiated phase change material is a monomer capable of undergoing free radical polymerization, selected from one or more mixtures of acrylonitrile, methacrylate, phosphorus-containing compound skeleton and ionic liquid; S3. Irradiate the precursor solution with γ-rays or an electron beam to induce a polymerization reaction, thereby obtaining a solid irradiated phase change electrolyte; The absorbed dose rate of the irradiation is 10~120 Gy / min, and the absorbed dose is 0.1~10 kGy.

[0006] This dosage range ensures that the irradiated phase change material undergoes sufficient free radical polymerization to form a three-dimensional cross-linked network structure, while avoiding excessive irradiation that could lead to polymer degradation.

[0007] Preferably, the carbonates include at least one of ethylene carbonate (EC), propylene carbonate (PC), dimethyl carbonate (DMC), diethyl carbonate (DEC), and ethyl methyl carbonate (EMC).

[0008] Preferably, the inert atmosphere is a nitrogen or argon atmosphere to prevent the electrolyte from reacting with moisture and oxygen in the air.

[0009] Preferably, in step S3, the irradiation is in-situ irradiation of the battery containing the precursor solution.

[0010] Preferably, the irradiated phase change material is selected from acrylonitrile, pentaerythritol tetraacrylate, methyl methacrylate, butyl methacrylate, divinyl phosphate, and 1-ethyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide.

[0011] Preferably, the radiation source that generates gamma rays is 60 Co source or 137 Cs source; the electron beam is generated by an electron accelerator with an energy of 0.1~10 MeV.

[0012] In a second aspect, the present invention provides an irradiated phase change electrolyte prepared by the method described in the first aspect.

[0013] Thirdly, the present invention provides a lithium-ion battery comprising the irradiated phase change electrolyte described in the second aspect.

[0014] Fourthly, this invention provides a method for testing the conductivity of an irradiated phase change electrolyte, comprising the following steps: sealing the irradiated phase change electrolyte in a battery casing while ensuring sufficient contact between the liquid and the electrodes; irradiating the battery casing containing the sealed phase change electrolyte solution with gamma rays or an electron beam to achieve in-situ phase change; then testing the ionic conductivity of the irradiated phase change electrolyte using electrochemical impedance spectroscopy (EIS); applying an AC voltage amplitude of 10 mV in the frequency range of 1 MHz to 1 Hz; and obtaining the resistance of the gel from the intersection of the curve and the horizontal axis in the Nyquist plot. R The total height H of the button battery is measured by a thickness gauge, the total thickness of the positive and negative electrode shells is d, the diameter D of the battery is measured by a ruler, and the ionic conductivity σ is calculated according to formula (1). The calculation is repeated three times and the average value is taken.

[0015] (1) Thermogravimetric analysis (TGA) is a test method for evaluating the thermal safety of phase change electrolytes.

[0016] Fifthly, the present invention provides a method for evaluating the thermal safety of the irradiated phase change electrolyte, comprising the following steps: weighing 10-15 mg of sample and placing it in an alumina crucible, heating it from 25°C to 800°C at a heating rate of 10°C / min under a nitrogen atmosphere, and recording the dynamic change curve of sample mass with temperature in real time; accurately extracting the temperature corresponding to a 5% mass loss as the thermal safety starting temperature T. 5% Meanwhile, the thermal runaway inhibition coefficient of residual carbon rate is defined as RCEC = (residual carbon rate at 800℃ / T). 5% ()×100, quantitatively characterizing the electrolyte's ability to suppress thermal runaway; A higher RCEC value indicates a stronger synergy between the electrolyte's residual carbon retention capacity and thermal stability at high temperatures, resulting in better thermal runaway suppression performance.

[0017] Compared with the prior art, the beneficial effects of the present invention are as follows: 1) The electrolyte is in liquid electrolyte and is suitable for lithium batteries: The electrolyte is in liquid state before irradiation. It has the same wettability and interfacial contact as liquid electrolyte, which can fully wet the electrode surface, reduce interfacial impedance, and is suitable for existing lithium battery manufacturing processes.

[0018] 2) Irradiation-induced in-situ phase change: Under the action of gamma rays or electron beams, the irradiated phase change material undergoes a free radical polymerization reaction, changing from a liquid phase to a solid phase. This eliminates the need for traditional curing processes such as high temperature, high pressure, or long-term aging, and the phase change process is rapid, controllable, and uniform.

[0019] 3) Electrochemical performance remains stable after electrolyte phase change: The solid electrolyte after phase change retains the high ionic conductivity of the liquid electrolyte, while the three-dimensional polymer network formed provides mechanical support and interfacial stability, and will not cause significant changes in the electrochemical performance of the battery.

[0020] 4) Phase change electrolytes can significantly improve the intrinsic safety performance of batteries: the changed solid electrolyte eliminates the leakage risk of liquid electrolytes, and the polymer network blocks the free flow of flammable organic solvents, which significantly improves the thermal stability and resistance to thermal runaway of batteries, thus achieving intrinsic safety. Attached Figure Description

[0021] Figure 1 The diagram shows a comparison of the electrolyte states before and after irradiation, where a is the liquid electrolyte before irradiation and b is the phase-change solid electrolyte after irradiation. Figure 2 Infrared spectra of phase change electrolytes and their corresponding monomers.

[0022] The horizontal axis represents wavenumber, in cm. -1 The vertical axis represents transmittance in %, with a and b representing divinyl phosphate and pentaerythritol tetraacrylate, respectively, and c representing the gel polymer after irradiation, used to demonstrate that a phase transition reaction occurred in the solution after irradiation.

[0023] Figure 3 AC impedance spectrum of phase change electrolyte.

[0024] The horizontal axis represents the real part of the impedance, in Ω (ohms), and the vertical axis represents the negative value of the imaginary part of the impedance, in Ω.

[0025] Figure 4 Thermogravimetric curve of phase change electrolyte.

[0026] The horizontal axis represents temperature, in units of... oC, the vertical axis is weight percentage, in wt%, a is the thermogravimetric curve of Comparative Example 1, and b is the thermogravimetric curve of Example 1. Detailed Implementation

[0027] The technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0028] Unless otherwise defined, all technical terms used herein have the same meaning as commonly understood by those skilled in the art. The technical terms used herein are for the purpose of describing particular embodiments only and are not intended to limit the scope of the invention.

[0029] Unless otherwise specified, all raw materials, reagents, instruments and equipment used in this invention can be purchased from the market or prepared by existing methods.

[0030] Example 1 The preparation method of phosphorus-containing compound skeleton-based irradiated phase change electrolyte is as follows: In a glove box under argon atmosphere, lithium hexafluorophosphate (LiPF6) was weighed and dissolved in a solvent consisting of ethylene carbonate (EC) and diethyl carbonate (DEC) in a 1:1 volume ratio to achieve a concentration of 1.0 mol / L. The solution was then heated to 25 °C. o Stirring at C for 2 hours yields an electrolyte system containing lithium salt.

[0031] S2 adds 30 g / L divinyl phosphate and 20 g / L pentaerythritol tetraacrylate (PETEA) as irradiation phase change materials to the above electrolyte system, and stirs for 4 hours to ensure thorough mixing and obtain a special phase change electrolyte.

[0032] S3 places the above-mentioned phase change special electrolyte into 60 Irradiation was performed in a Co gamma-ray irradiation chamber at an absorbed dose rate of 50 Gy / min, with an absorbed dose of 2 kGy. After irradiation, the radiation was applied at 60°C. o The irradiated phase change solid electrolyte was obtained by vacuum drying at C for 12 h.

[0033] Infrared spectroscopy tests were performed on the electrolytes before and after irradiation (e.g.) Figure 2 As shown), after irradiation at 1720 cm -1 The characteristic absorption peak of the ester group is enhanced at 1630 cm⁻¹. -1The disappearance of the characteristic peak of the C=C double bond indicates that divinyl phosphate and PETEA underwent a cross-linking polymerization reaction, forming a gel polymer network with a phosphorus-containing backbone. Further testing of ionic conductivity yielded the AC impedance spectrum of the phase change electrolyte, as shown below. Figure 3 As shown, its ionic conductivity at room temperature is calculated to be 6.86 mS / cm. -1 .

[0034] To verify that phase change electrolytes can significantly improve the intrinsic safety performance of batteries, thermogravimetric analysis (TGA) was performed on the irradiated phase change electrolyte. For example... Figure 4 As shown, the thermal stability of the sample after phase change is significantly improved compared to control sample 1, with a significantly higher initial thermal safety temperature and carbon residue rate. Further calculations yielded RCEC values ​​of 8.2 and 5.6 for Example 1 and control sample 1, respectively, fully demonstrating that phase change electrolytes can significantly improve the intrinsic safety performance of batteries.

[0035] Example 2 The preparation method of acrylonitrile-based irradiated phase change electrolyte is as follows: S1: Under a nitrogen atmosphere, weigh 0.8 mol / L lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), dissolve it in propylene carbonate (PC), and 30 o Stirring at C for 3 h yields an electrolyte system containing lithium salt.

[0036] S2: Add acrylonitrile with a mass concentration of 40 g / L as the irradiation phase change material, stir for 3 h to mix it evenly, and obtain a phase change special electrolyte.

[0037] S3: The electrolyte was irradiated using an electron accelerator with an energy of 2 MeV at an absorbed dose rate of 80 Gy / min and an absorbed dose of 5 kGy. After irradiation, the electrolyte was then subjected to a 50°C irradiation treatment. o Drying at C for 8 h yields a polyacrylonitrile-based irradiated phase change solid electrolyte.

[0038] Example 3 The preparation method of methacrylate-based irradiated phase change electrolytes is as follows: S1: In a glove box protected by an argon atmosphere, dissolve 1.2 mol / L lithium bis(oxalatoborate) (LiBOB) in ethyl methyl carbonate (EMC) at 25°C. o Stir for 2 hours (C).

[0039] S2: Add methyl methacrylate (MMA) at a mass concentration of 25 g / L and butyl methacrylate at a mass concentration of 15 g / L, and stir for 4 h to mix evenly.

[0040] S3: Adopt 60Irradiation was performed using a Co γ-ray source at an absorbed dose rate of 30 Gy / min and an absorbed dose of 1 kGy. The irradiated product was a polymethacrylate-based irradiated phase change solid electrolyte.

[0041] Example 4 The preparation method of the composite irradiated phase change electrolyte is as follows: S1: Under an argon atmosphere, 0.6 mol / L LiFSI and 0.4 mol / L LiPF6 were mixed and dissolved in a mixed solvent with EC:DEC:DMC = 1:1:1 (volume ratio), and the solution was heated to 25 °C. o Stir for 2 hours (C).

[0042] S2: Add 20 g / L acrylonitrile, 20 g / L pentaerythritol tetraacrylate and 10 g / L ionic liquid 1-ethyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide (EMIM-TFSI) in sequence, and stir for 5 h to mix thoroughly.

[0043] S3: Irradiated using an electron accelerator with an energy of 5 MeV, an absorbed dose rate of 100 Gy / min, and an absorbed dose of 3 kGy. The resulting composite irradiated phase-change solid electrolyte exhibits both high ionic conductivity and excellent thermal stability.

[0044] The above description is merely an embodiment of the present invention and is not intended to limit the invention. Those skilled in the art can make various modifications to the technical solutions in the embodiments based on the above description. It is neither necessary nor possible to exhaustively describe all possible implementations. Any modifications, variations, substitutions, etc., made based on the technical content disclosed in this invention are equivalent to equivalent implementations and should be included within the protection scope of this invention.

[0045] Comparative Example 1 The same lithium salt electrolyte (1.0 mol / L LiPF6 in EC / DEC = 1:1) as in Example 1 was prepared, but without the addition of irradiated phase change material or irradiation treatment, and was used as a baseline comparative example.

[0046] Comparative Example 2 The electrolyte was prepared according to the same formulation as in Example 1, but the irradiated absorbed dose was increased to 20 kGy (exceeding the protection scope of this invention). This comparative example demonstrates that excessively high irradiation doses lead to excessive cross-linking and degradation of the polymer, a significant decrease in ionic conductivity, and severe deterioration of electrochemical performance, indicating the technical necessity of the dose range (0.1~10 kGy) defined in this invention.

[0047] Comparative Example 3 The electrolyte was prepared using the same formulation as in Example 1, but the absorbed radiation dose was reduced to 0.05 kGy (below the protection range of this invention). This comparative example demonstrates that excessively low radiation doses cannot fully polymerize the irradiated phase change material, the electrolyte remains liquid, and a solid gel structure cannot be formed. Therefore, the safety performance is not improved, illustrating the necessity of the lower dose limit (0.1 kGy) of this invention.

[0048] The samples prepared in Examples 2-4 and Comparative Examples 1-3 were tested according to the methods and test conditions described in Example 1, and the results are recorded in Table 1 along with the test results of Example 1.

[0049] Table 1. Performance test results of samples prepared in Examples 1-4 and Comparative Examples 1-3 Example Ionic conductivity (mS / cm) RCEC Example 1 6.86 8.2 Example 2 6.38 7.4 Example 3 6.24 7.9 Example 4 5.97 7.5 Comparative Example 1 7.08 5.5 Comparative Example 2 4.34 8.4 Comparative Example 3 6.73 5.8 As can be seen from Table 1: (1) Although the ionic conductivity of Examples 1 to 4 is slightly lower than that of the liquid electrolyte (Comparative Example 1), the RCEC is much higher than that of Comparative Example 1, and the safety is significantly enhanced.

[0050] (2) Comparative Examples 2 and 3 demonstrate that the irradiation dose range (0.1~10 kGy) defined by the present invention is a key technical parameter to ensure "successful phase transition and no performance degradation".

[0051] The above description is merely an embodiment of the present invention and is not intended to limit the invention. Those skilled in the art can make various modifications to the technical solutions in the embodiments based on the above description. It is neither necessary nor possible to exhaustively describe all possible implementations. Any modifications, variations, substitutions, etc., made based on the technical content disclosed in this invention are equivalent to equivalent implementations and should be included within the protection scope of this invention.

Claims

1. A method for preparing an irradiated phase change electrolyte, characterized in that, Includes the following steps: S1: Lithium salt is dissolved in ester organic compounds under an inert atmosphere to obtain an electrolyte containing lithium salt; the lithium salt concentration is 0.5–2 mol / L; The lithium salt is one or a mixture of two or more of lithium hexafluorophosphate, lithium dioxaborate, lithium tetrafluoroborate, lithium bis(difluorosulfonyl)imide, and lithium bis(trifluoromethylsulfonyl)imide. The ester organic compounds are one or more of carbonates, carboxylic acid esters, and vinylene carbonates; S2: Add the irradiated phase change material to the electrolyte and mix thoroughly to obtain a precursor solution; the mass concentration of the irradiated phase change material in the precursor solution is 20~60 g / L; The irradiated phase change material is a monomer capable of undergoing free radical polymerization, selected from one or more mixtures of acrylonitrile, methacrylate, phosphorus-containing compound skeleton and ionic liquid; S3. Irradiate the precursor solution with γ-rays or an electron beam to induce a polymerization reaction, thereby obtaining a solid irradiated phase change electrolyte; The absorbed dose rate of the irradiation is 10~120 Gy / min, and the absorbed dose is 0.1~10 kGy.

2. The method for preparing irradiated phase change electrolyte according to claim 1, characterized in that, The carbonates include at least one of ethylene carbonate, propylene carbonate, dimethyl carbonate, diethyl carbonate, and methyl ethyl carbonate.

3. The method for preparing irradiated phase change electrolyte according to claim 1, characterized in that, The inert atmosphere is a nitrogen or argon atmosphere.

4. The method for preparing irradiated phase change electrolyte according to claim 1, characterized in that, In step S3, the irradiation is to irradiate the battery containing the precursor solution in situ.

5. The method for preparing an irradiated phase change electrolyte according to claim 1, characterized in that, The irradiated phase change material is selected from acrylonitrile, pentaerythritol tetraacrylate, methyl methacrylate, butyl methacrylate, divinyl phosphate, and 1-ethyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide.

6. The method for preparing irradiated phase change electrolyte according to claim 1, characterized in that, The radiation source that produces gamma rays is 60 Co source or 137 Cs source; the electron beam is generated by an electron accelerator with an energy of 0.1~10 MeV.

7. An irradiated phase change electrolyte prepared by the method of any one of claims 1 to 6.

8. A lithium-ion battery comprising the irradiated phase change electrolyte of claim 7.

9. A method for testing the conductivity of an irradiated phase change electrolyte as described in claim 7, characterized in that, The process includes the following steps: sealing the irradiated phase change electrolyte in a battery casing; irradiating the battery casing with the sealed phase change electrolyte solution using gamma rays or an electron beam to achieve in-situ phase change; then testing the ionic conductivity of the irradiated phase change electrolyte using AC impedance spectroscopy (ACIS) in the frequency range of 1 MHz to 1 Hz; and obtaining the gel resistance from the intersection of the curve and the horizontal axis in the Nyquist plot. R The total height H of the button cell was measured by a thickness gauge, and the total thickness d of the positive and negative electrode shells was measured by a ruler. The ionic conductivity σ was calculated according to formula (1). (1)。 10. A method for evaluating the thermal safety of the irradiated phase change electrolyte of claim 7, characterized in that, The process includes the following steps: Under an inert atmosphere, the temperature is increased to 800℃ at a rate of 10℃ / min, and the dynamic change curve of sample mass with temperature is recorded in real time; the temperature at which 5% mass loss is extracted is taken as the thermal safety starting temperature T. 5% Meanwhile, the thermal runaway inhibition coefficient of residual carbon rate is defined as RCEC = (residual carbon rate at 800℃ / T). 5% ()×100, quantitatively characterizing the electrolyte's ability to suppress thermal runaway.